Analyzing Engineering-Related Delays Using Quality Function Deployment in Construction Projects - Salah Aldeen Salah (Salehan Institute of Higher Education, 2020)
This paper presents a methodology for analyzing engineering-related delays in construction projects using Quality Function Deployment (QFD). The steps of the QFD technique are combined in the quality and control policy. A reference matrix based on the literature review is constructed with engineering delays and a survey of all parties involved in construction projects. The QFD matrix aids in identifying the most significant reasons for delays and claims in the construction projects. For the identified reasons, solutions have been developed to limit or reduce them. The mean sources of construction delays include engineering, construction, financial/economic, management/administrative, and force majeure. This paper presents a knowledge-based QFD technique dedicated to engineering-related delays. Three categories of Engineering-related delays are considered in the proposed system. These categories are 1) design development, 2) workshop drawings, and 3) project party’s changes delays. The knowledge of the QFD matrix is acquired from literature, Federation International des Ingenious - Conseils (FIDIC) contract forms, domain experts, as well as a questionnaire survey. Three classes of participants (i.e., consultants, contractors, and Employers) have been approached to get their feedback on the cases of engineering-related delays. The proposed approach helps to limit or reduce delays in construction projects caused by the engineer. Accordingly, it was concluded to the most important reasons that led to the delay of construction projects related to the engineer, using QFD.